Histological type and typing of breast carcinomas and the WHO classification changes over time - Cserni, Gábor (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2020)
The World Health Organization’s new classification of breast tumors has just been published. This review aims to examine the morphological categorization of breast carcinomas which is still principally based on histological features and follows the traditions of histological typing. It gives a subjective and critical view on the WHO classifications and their changes over time, and describes the changes related to some of the most common or challenging breast carcinomas: in situ carcinomas, invasive breast carcinomas of no special type, lobular, cribriform, tubular, mucinous, papillary, metaplastic carcinomas and carcinomas with medullary pattern and those with apocrine differentiation are discussed in more details. Although the 5th edition of the classification is not perfect, it has advantages which are mentioned along with problematic issues of classifications.